Fragility, Conflict, and Migration: A new CGIAR Initiative for a fragile world - Kosec, Katrina; Läderach, Peter R.D.; Ruckstuhl, Sandra (CGIAR, 2023)
The Fragility, Conflict, and Migration (FCM) Initiative is the newest addition in the CGIAR research portfolio. It officially started in April and is having two launch events in May: in Abuja, Nigeria, on May 11 and Amman, Jordan, on May 24. In this interview, Initiative Lead Katrina Kosec and Co-Leads Peter Läderach and Sandra Ruckstuhl answer a few questions about what the FCM Initiative is about and why the issues of fragility, conflict, and migration are critical for achieving CGIAR goals.